Diseño de la planificación de requerimiento de material (MRP) para la empresa Carpintería Maderisah. (2024)
This research project proposes a materials requirements planning (MRP) design for the carpentry company Maderisah, a company dedicated to the custom-order manufacturing of doors and closets based on organic and synthetic wood. It consists of efficiently managing and planning the production of goods. In order to optimize productivity, reduce order delivery time and achieve customer satisfaction. For the development of the objectives, a diagnosis of the company was primarily carried out in order to know the current state of its production system, making the internal personnel of the company known and also identifying the deficiencies that arise, to achieve better quality. We continue with a forecast that shows us the anticipated estimate of the demand for materials necessary for production, together with an aggregate plan that allows us to know the times and requirements needs, this facilitates more efficient management of resources, minimizes costs and ensures that production meets demand effectively. We proceed to design the MRP, in order to plan the requirements for specific materials and establish the cost-benefit relationship of the MRP as a proposed improvement for the company, making known the costs, the current inventory, etc. And as the last development of the objective we find programming in Microsoft Excel where the aim is to make it easier for the worker to keep track of the requirements that are needed in each period.